Effect of an immunosuppressive serum α-2-glycoprotein with ribonuclease activity on the proliferation of human lymphocytes in culture - Milton, J. D. (1971)
A serum α-2-glycoprotein (Fraction C) which has previously been shown to have immunosuppressive properties and to possess ribonuclease activity, has an inhibitory effect on the in vitro proliferation of human lymphocytes stimulated by PHA, PPD or allogeneic cells. A linear dose response curve is obtained for the inhibition of maximally stimulated PHA cultures, whereas it is non-linear for inhibition of antigenically stimulated cultures. Preincubation with Fraction C has no effect on subsequent stimulation with PHA, but does inhibit subsequent stimulation with PPD or allogeneic cells. It is suggested that this difference in sensitivity to Fraction C of these two types of lymphocyte culture may be due either to an effect on phagocytic cells which are essential for PPD and mixed lymphocyte cultures, or that different lymphocytes are involved in the two sorts of culture. Fraction C does not appear to have any direct competitive effect on PHA stimulation. In PHA cultures there is no short period of high sensitivity to Fraction C, and the inhibitory effect is to a large extent cumulative with time. Nevertheless the period immediately after initiation of the cultures does have a somewhat greater sensitivity to Fraction C than later periods. The possible application of these data to design of protocols for better achievement of in vivo immunosuppression is discussed.